The hull-waterjet interaction of a planing trimaran. (1st February 2021) - Jiang, Jiabing; Ding, Jiangming
Abstract: Hull-waterjet interaction is a key point in the research of waterjet-propelled crafts. The previous researches on hull-waterjet interaction mainly aim at displacement ships and planing monohulls, and mostly focus on speeds of FrL  < 1.5, which has not included maximum speed of waterjet-propelled crafts in current engineering practice. Based on numerical and experimental research, this paper studies the hull-waterjet interaction of a high speed planing trimaran in the speed range of 0.68 < Fr▽ <6.16 (0.32L  < 2.87), including analysis of thrust deduction and interaction efficiency. The numerical simulation is based on the Reynolds-Averaged Navier-Stokes (RANS) equation with the SST k-ω turbulence model. As for semi-planing and planing state of this planing trimaran, the local effect of waterjet suction and jet is helpful to reduce the resistance while the global hull-attitude change will cause the increment on resistance of self-propelled hull. Compared with monohulls, the negative resistance increment fraction of this trimaran occurs at higher speed. The jet system thrust deduction fraction is always negative at high speeds and increases almost linearly with speed growth. The interaction efficiency is larger than 1.0 when Fr▽ >2.0, indicating that the hull-waterjet interaction of this trimaran has positive effects on propulsion performance at semi-planing and planing state. Highlights: The hull-waterjet interaction of a planing trimaran has been analyzed, differing from displacement ship and planing monohull. The thrust deduction fraction and interaction efficiency has been calculated and discussed in a wider speed range of 0.68 < Fr▽ <6.16. The local effect of waterjet action and global effect of hull attitude change are quantified as fractions and analyzed separately.